Strategi Peningkatan Mutu Belajar Mengajar Sekolah Berbasis Pondok Pesantren di Smk Darussalam Subah di Desa Kemiri Barat Kecamatan Subah Kabupaten Batang - Latif, Helmi Abdul; LAILA, MILADIA; Aliyah, Nadia Sofiyatul; Azizah, Luthfiyah; Hakim, M.Luthfil; Nadhiroh, Hafidhotun; Mustaszar, Amir; Nafisah, Lubna Aula; Kamelia, Aisyah (LPPM Sekolah Tinggi Islam Kendal, 2025)
This study aims to describe strategies for improving the quality of teaching and learning in Islamic boarding school-based education at SMK Darussalam Subah. The background of this research is based on the need to integrate pesantren values with the formal education system in order to achieve excellent learning outcomes. This study employed a qualitative approach with observation, interviews, and documentation techniques. The findings reveal several key strategies in improving the quality of learning, including strengthening teacher competencies through regular training and coaching programs, implementing an integrated learning model that combines the national curriculum with the pesantren curriculum, cultivating a religious culture within the school environment, and optimizing the role of pesantren caretakers and teachers as role models in students’ character development. In addition, the implementation of pesantren-based school management, which emphasizes discipline, morality, and responsibility, has a positive impact on students’ learning motivation. The study concludes that the strategies applied by SMK Darussalam Subah are effective in improving the quality of teaching and learning while fostering a balance between academic, spiritual, and moral aspects of students.